The impact of therapeutic ankle taping and foot posture on the kinematics of the knee and ankle while running - Cava, D.; Kivi, D. M. R.; Sanzo, P.; Zerpa, C. (ISBS Proceedings Archive (Michigan), 2020)
Overpronation is a misalignment of the calcaneus, contributing to overuse injuries in runners. Taping may control the position of the calcaneus to correct foot pathologies associated with overpronation. The purpose of this study was to explore the effect of therapeutic ankle taping and foot posture on the kinematics of the knee and ankle during running in participants with neutral and pronated foot types. Forty healthy participants ran on a treadmill with the application of Kinesio Tape®, Leuko Tape®, and no tape. A significant main effect for foot posture indicated that participants with a pronated foot type (p=.03) ran with a decreased amount of plantarflexion at the toe off phase of running when compared to a neutral foot type for all taping conditions. As plantarflexion occurs at toe off to propel the runner to the swing phase, a more rigid taping technique may be beneficial to provide support to the calcaneus.